2014
DOI: 10.1517/13543784.2014.902050
|View full text |Cite
|
Sign up to set email alerts
|

The potential of pralatrexate as a treatment of peripheral T-cell lymphoma

Abstract: None of the treatments commonly used today have given satisfactory results. Pralatrexate seems to be one of the most promising agents in the treatment of patients with PTCL. Future efforts should be focused on better understanding the molecular pathogenesis of PTCL and on specific trials for different PTCL subtypes using rational drug combinations that include pralatrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Pralatrexate is an anti-folate 9, 10 with demonstrated tolerability and activity in subjects with relapsed/refractory peripheral T cell lymphoma (PTCL) and CTCL However, the approved dose of pralatrexate for PTCL is 30 mg/m2 weekly for 6 of 7 weeks. 10, 11 In a CTCL specific study, the dose of 15 mg/m 2 pralatrexate given weekly 3 of 4 weeks was identified as active and was better tolerated than the full standard dosing with an overall response rate of 45% among patients with relapsed or refractory disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pralatrexate is an anti-folate 9, 10 with demonstrated tolerability and activity in subjects with relapsed/refractory peripheral T cell lymphoma (PTCL) and CTCL However, the approved dose of pralatrexate for PTCL is 30 mg/m2 weekly for 6 of 7 weeks. 10, 11 In a CTCL specific study, the dose of 15 mg/m 2 pralatrexate given weekly 3 of 4 weeks was identified as active and was better tolerated than the full standard dosing with an overall response rate of 45% among patients with relapsed or refractory disease.…”
Section: Introductionmentioning
confidence: 99%
“…10, 11 In a CTCL specific study, the dose of 15 mg/m 2 pralatrexate given weekly 3 of 4 weeks was identified as active and was better tolerated than the full standard dosing with an overall response rate of 45% among patients with relapsed or refractory disease. 12 The dose limiting toxicity for pralatrexate is mucositis; 12 bexarotene induces central hypothyroidism and hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 99%
“…Pralatrexate is the first drug to have been approved by the US Food and Drug Administration specifically for treating patients with relapsed or refractory PTCL. 3 As a folate analog metabolic inhibitor, pralatrexate competitively inhibits dihydrofolate reductase and reduces cellular levels of thymidine monophosphate, which prevents the cell from synthesizing genetic material and triggers it to undergo apoptosis. 4 The agency's approval of pralatrexate was based on results from the PROPEL study, which is possibly the largest prospective study conducted in patients with relapsed or refractory PTCL (109 evaluable patients).…”
mentioning
confidence: 99%
“…It easily enters malignant cells with overexpression of folate membrane transporters and is efficiently polyglutamylated, which increases intracellular half-life. Owing to this unique nature, the agent has shown durable responses in highly refractory cases even after discontinuation ( 6 7 ). It has little cumulative toxicity and can be administered continuously to patients of old age or ineligible for consolidative stem cell transplantation.…”
mentioning
confidence: 99%